Return on Equity and Earning per Share as Market Value Added Determinants of Infrastructure Companies listed on the Indonesia Stock Exchange - Saputra, Fendi; Zulkifli (International Journal of Social and Management Studies, 2022)
Adequate infrastructure development can affect the attractiveness of the investment climate in Indonesia. However, the development of Indonesia's infrastructure is not easy because Indonesia is an archipelago that is more complex. The government must be aware of the importance of improving the state of infrastructure so that the investment and business climate becomes more attractive. This study aims to identify and analyze return on equity and earnings per share as determinants of market value added for infrastructure companies listed on the Indonesia Stock Exchange. Data analyzed 2017-2019 period. Types of quantitative research. The population of all infrastructure companies, the sample criteria are companies that are consistently listed on the Indonesia Stock Exchange during the study period, using purposive sampling technique. The analysis technique is panel data regression analysis. The results of the study prove that return on equity and earnings per share simultaneously affect market value added. However, partially the return on equity and earnings per share do not affect the market value added. This research is then directed to add internal and/or external factors as well as those that can influence market value added to use a sample of companies such as mining, manufacturing, finance, property and real estate, agriculture and trade companies, not only analyzing the infrastructure company sector.